Amharische Syntax in späten Originalwerken des Gǝʿǝz - Sima †; herausgegeben von Michael Waltisberg, Alexander (Aethiopica, 2010)
[Wal.: The Gǝʿǝz syntax of the Sälamat, short poems which were added to the text of the Synaxarium at a later date, shows features that are known from modern Ethiosemitic languages, especially Amharic. This applies in particular to the preposing of the adjective and the genitive within the noun phrase, the final position of the verb in the matrix as well as the dependent clause, the fronting of dependent clauses before their matrix clause and the occasional use of circumpositions. In addition, as a specific poetic feature, the use of the feminine relative marker instead of the masculine is briefly demonstrated. The late Alexander Sima discusses all these phenomena and presents numerous examples from the Sälamat.]